Antonio Alvar Ezquerra, Exilio y elegía latina entre la Antigüedad y el Renacimiento, Huelva, Universidad de Huelva, 1997, 205 pp. (Minerva, 2019)
Review: Antonio Alvar Ezquerra, Exilio y elegía latina entre la Antigüedad y el Renacimiento, Huelva, Universidad de Huelva, 1997, 205 pp.